The Santa Clara Strength of Religious Faith Questionnaire: Confirmatory factor analysis. - MC GUCKIN, CONOR (My University, 2001)
Within contemporary psychology there is increasing interest in the role of religion on behaviour and psychological functioning. Such interest can be attested to by the growth in the number of pertinent books and articles that have been published and also the development of new self-report measures of religiosity. The Santa Clara Strength of Religious Faith Questionnaire is one such recently developed measure. It is a brief self-report measure comprising 10 items that were designed to measure strength of religious faith regardless of religious denomination or affiliation. Although Plante and Boccaccini (1997a, 1997b) have provided some preliminary evidence for the reliability and validity of the scale, the factor structure of the scale has not yet been examined. The aim of the present paper was to confirm the factor structure of the scale. The hypothesised one-factor model was tested using confirmatory factor analytic methods. Data from a sample of 106 Northern Irish undergraduate university students were examined using confirmatory factor analytic methods. A one-factor model was tested and accepted on the basis of fit statistics, therefore supporting the hypothesised unidimensional structure of the scale. The present results provide further evidence that the Santa Clara Strength of Religious Faith Questionnaire is psychometrically sound and therefore it can be recommended for further use by researchers interested in the construct of strength of religious faith.
PUBLISHED
Keywords: Santa Clare questionaire